Effect of Mild Salinity Stress on the Growth, Fatty Acid and Carotenoid Compositions, and Biological Activities of the Thermal Freshwater Microalgae Scenedesmus sp. - Wiem Elloumi; Ahlem Jebali; Amina Maalej; Mohamed Chamkha; Sami Sayadi (Biomolecules, 2020)
Carotenoids have strong antioxidant activity as well as therapeutic value. Their production has been induced in algae under stressful culture conditions. However, the extreme culture conditions lead to the Programmed Cell Death (PCD) of algae, which affects their growth and productivity. This study was performed to evaluate the effect of salinity on the physiological and biochemical traits of Scenedesmus sp., thermal freshwater microalgae from Northern Tunisia. It was cultured under different NaCl concentrations ranging from 0 to 60 g/L. Results showed a good growth and high contents of total chlorophyll and carotenoids in Scenedesmus sp. cultured at 10 g/L of NaCl (salt-stressed 10 (Ss10)). The pigment composition of the Ss10 extract was acquired using HPLC–MS, and showed that the carotenoid fraction is particularly rich in xanthophylls. Moreover, the antioxidant (DPPH and FRAP) and enzymatic inhibition (tyrosinase and elastase) activities of the Ss10 extract were higher compared to those of the control culture. In addition, the cytotoxicity test on B16 cells showed that the Ss10 extract was non-toxic for all tested concentrations below 100 µg/mL. It also showed a rich unsaturated fatty acid (FA) composition. Therefore, these findings suggest that Scenedesmus sp. strain cultivated under mild stress salinity could be a source of biomolecules that have potential applications in the nutraceutical and cosmeceutical industries.